Nitric Oxide Deficiency in Mitochondrial Disorders: The Utility of Arginine and Citrulline - Almannai, Mohammed; El-Hattab, Ayman W. (Frontiers in Molecular Neuroscience, 2021)
Mitochondrial diseases represent a growing list of clinically heterogeneous disorders that are associated with dysfunctional mitochondria and multisystemic manifestations. In spite of a better understanding of the underlying pathophysiological basis of mitochondrial disorders, treatment options remain limited. Over the past two decades, there is growing evidence that patients with mitochondrial disorders have nitric oxide (NO) deficiency due to limited availability of NO substrates, arginine and citrulline; decreased activity of nitric oxide synthase (NOS); and NO sequestration. Studies evaluating the use of arginine in patients with mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) presenting with stroke-like episodes showed symptomatic improvement after acute administration as well as reduction in frequency and severity of stroke-like episodes following chronic use. Citrulline, another NO precursor, was shown through stable isotope studies to result in a greater increase in NO synthesis. Recent studies showed positive response of arginine and citrulline in other mitochondrial disorders besides MELAS. Randomized-controlled studies with larger number of patients are warranted to better understand the role of NO deficiency in mitochondrial disorders and the efficacy of NO precursors as treatment modalities in these disorders.